Prader-Willi Syndrome and Atonic Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
A 2.5-year-old boy with Prader-Willi syndrome and a history of neonatal superior sagittal sinus thrombosis developed a febrile seizure and new onset atonic drop seizures originating in the parasagittal region, as reported from Children's Hospital, Boston.